solve for x.

2x - 4x - 3 =-27

1 answer

To solve for \( x \) in the equation \( 2x - 4x - 3 = -27 \), we can follow these steps:

  1. Combine like terms on the left side of the equation: \[ 2x - 4x = -2x \] So the equation simplifies to: \[ -2x - 3 = -27 \]

  2. Next, add 3 to both sides of the equation to isolate the term with \( x \): \[ -2x - 3 + 3 = -27 + 3 \] This simplifies to: \[ -2x = -24 \]

  3. Finally, divide both sides by -2: \[ x = \frac{-24}{-2} \] Thus, we get: \[ x = 12 \]

So the solution is \( x = 12 \).